Cytokine networks in the pathophysiology of inflammatory bowel disease - Friedrich, M; Pohin, M; Powrie, F (Cell Press, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the gastrointestinal tract. Cytokine-targeted therapies have transformed the treatment of IBD, providing control of symptoms and longer relapse-free periods. However, many patients fail to respond, highlighting the need for therapies tailored to the underlying cell and molecular disease drivers. Here we discuss the progression of IBD from the perspective of remodeling of cytokine networks. We place well-established and under-studied cytokine modules in the context of cellular interactions, their dynamic regulation in early and late stages of disease (i.e., fibrosis), and their current and potential use in the clinic. Examining how particular cytokine networks drive distinct features and phases of IBD will shed light on the etiology of IBD and provide a basis for more effective treatments.